2007
DOI: 10.4028/www.scientific.net/ssp.124-126.1585
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Silicate Glasses and Glass-Ceramics Containing EAF Dust in Acidic Solution

Abstract: The corrosion behavior of glass and glass-ceramics fabricated with silicate glass frit mixed with 50~70 wt% EAF dust in the acidic solution was analyzed by both heavy metal leaching test and microstructural observation. The crystallization temperature, Tc of glassy specimens was around 850 measured by DTA and the heat treatment temperature to crystallize a glassy specimen was selected as 950 / 1 hr. The spinel crystal peaks were found in XRD analysis for the glass containing dust > 60 wt%. For the glass-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Pelino [53] describes vitrification of zinc dust electric-arc furnace with the addition of cullet and sand. On the other hand, Kim et al [54] added steelmaking waste to 30-50% calcium borosilicate, which melts at 1350ºC. Attempts at vitrification of slag with the addition of sand and dolomite were also conducted by Duca et al [55], who found that the product can be used as a replacement for pottery.…”
Section: Vitrification Of Wastementioning
confidence: 99%
“…Pelino [53] describes vitrification of zinc dust electric-arc furnace with the addition of cullet and sand. On the other hand, Kim et al [54] added steelmaking waste to 30-50% calcium borosilicate, which melts at 1350ºC. Attempts at vitrification of slag with the addition of sand and dolomite were also conducted by Duca et al [55], who found that the product can be used as a replacement for pottery.…”
Section: Vitrification Of Wastementioning
confidence: 99%